(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
The joints biomechanic study of the horse’s finger and that of boulet, in particular, dresses an interest as for the dynamic and static functions. In order to visualize the functional parts of the thoracic member’s region, we have tried to appreciate the maximal amplitude of the finger’s movement to the support. The gotten results reveal, however, the individual variation existence.